2017
DOI: 10.1111/ijn.12563
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of patients developed delirium after coronary artery bypass grafting is determined by cognitive function after discharge: A cross‐sectional study

Abstract: The QoL of patients developed delirium after CABG is determined by cognitive function after discharge. Necessary strategies should be implemented to prevent POD and declined cognitive function, especially in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…The former, which is considered a strong predictor of POCD development, usually occurs within the first 3 postoperative days [14,15]. However, POCD occurs at the end of the first week and has no effect on consciousness, and its duration may be significantly prolonged [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The former, which is considered a strong predictor of POCD development, usually occurs within the first 3 postoperative days [14,15]. However, POCD occurs at the end of the first week and has no effect on consciousness, and its duration may be significantly prolonged [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Najafi, Sheikhvatan, Montazeri, and Sheikhfathollahi (2008) found that older patients had a higher score in the psychological dimension of HRQoL. In contrast, Chen et al (2017) patients had higher levels of depression than males, and Lavdaniti et al (2015) reported that social role was affected by both the gender and the occupational status of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are few studies on the medium-term and long-term consequences of POCD and POD on patients' QOL and autonomy. 12,13 In addition, with regard to heart surgery, cognitive changes are still mainly studied in the framework of coronary artery bypass graft. 12 The main objective of this study was to evaluate the role of POD in poor evolution at three years after cardiac surgery including poor QOL and dependence and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, with regard to heart surgery, cognitive changes are still mainly studied in the framework of coronary artery bypass graft. 12 The main objective of this study was to evaluate the role of POD in poor evolution at three years after cardiac surgery including poor QOL and dependence and mortality. Then, we researched factors, which explicated a poor patient evolution, especially influence of postoperative cognitive trajectories.…”
Section: Introductionmentioning
confidence: 99%